PENGARUH DESAIN PRODUK DAN PROMOSI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA OLEH-OLEH THE PANASDALAM - Septihayati, Yulia; Raskadi, Raskadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
This study is motivated by the increasing competition in the creative souvenir fashion industry, which requires businesses to gain competitive advantages through attractive product design and effective promotional strategies, particularly via Instagram social media. This study aims to analyze the influence of product design and Instagram promotion on consumer purchase decisions for The Panasdalam souvenir apparel products. The research employs a quantitative method with a descriptive-verificative design. Data were collected through questionnaires distributed to 120 consumers of The Panasdalam and analyzed using multiple linear regression, t-tests, and F-tests. The results indicate that product design and Instagram promotion have a positive and significant effect on consumer purchase decisions, both partially and simultaneously. The coefficient of determination of 0.400 indicates that 40 percent of the variation in purchase decisions is explained by product design and Instagram promotion. This study recommends improving product design quality and optimizing Instagram promotion to enhance consumer purchase decisions. Keywords: Product Design; Instagram Promotion; Purchase Decision; The Panasdalam